362. CLINICAL VALUE AND EFFICACY INDEX OF LYMPHADENECTOMY FOR THORACIC ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (24th September 2022) - Li, Kexun; Leng, Xue Feng; Du, Kunyi; Liu, Kun; He, Wenwu; Wang, Qifeng; Luo, Xi; Wang, Chenghao; Wang, Kangning; Liu, Guangyuan; Wei, Xing; Li, Haojun; et al.
Abstract: Esophageal squamous cell carcinoma (ESCC) has high mortality in China. The cornerstone of treatment for resectable esophageal cancer is still surgery. It is vital to find the regularity of lymph node metastasis and the value of dissection for thoracic ESCC in China, to provide a basis for accurate staging and the relationship between overall survival (OS) and lymph node dissection. Cases were collected from 2957 patients in Sichuan Cancer Hospital & Institute Esophageal Cancer Case Management Database (SCH-ECCM Database) from January 2010 to August 2017. The stations of lymph node were referenced according to CSCO diagnosis and treatment guidelines and JES, 11th Ed. According to the frequency and patient's survival of metastases to each station of investigated tumor location were used to calculate the Efficacy Index (EI). EI was calculated by multiplying the frequency (%) and 5-year survival rate of metastases (%) in patients, and then dividing by the number of 100. The median follow-up time was 59.5 months. The EI was high in supraclavicular and mediastinal zones in patients with upper esophageal tumors, and the EI of 106recR was 13.72, which was the highest among lymph node stations. The EI was high in mediastinal zone followed by celiac and supraclavicular zones in patients with middle esophageal tumors, 104R with EI of 15.54 was the highest among lymph node stations. As for patients with lower esophageal tumors, the EI was high in celiac zone followed by mediastinal zones, the EI of left gastric artery was 10.86, over every lymph node stations. The EI of right recurrent nerve lymph nodes is the highest in upper esophageal cancer, as for middle esophageal cancer right supraclavicular lymph nodes had high metastasis rate and EI, but the left gastric lymph nodes had high metastasis rate and EI in the lower esophageal cancer. Although the lymph node metastasis rate of ESCC is still high, the more efficient lymphadenectomy should be considered based on further studies.